Post-Pandemic Digital Transformation in Zakat Management: Insights from Maqasid Syari'ah in South Kalimantan - Maulida, Sri; Amruzi, Fahmi Al; Hakim, Budi Rahmat; Beik, Irfan Syauqi (El-Mashlahah, 2024)
The background of this study highlights significant social changes related to the digitalization of zakat (almsgiving) management, particularly in the context of post-Covid-19 pandemic recovery. The research aimed to examine the digital transformation in zakat management following the pandemic from a maqasid syari'ah perspective. The study employed an empirical legal research approach, with data collected through interviews. Respondents were academics, muzakki, and staff from zakat management organizations (BAZNAS and LAZNAS) in South Kalimantan Province. The interview data were transcribed and analyzed qualitatively using a coding process facilitated by Atlas.ti software, version 8. The findings found that digitalization of zakat management, classified as an element of hajiyyah, serves as a solution to support the fulfillment of Islamic legal obligations, prevent religious violations, provide ease in human life, and expand access to zakat, particularly during the post-pandemic recovery phase.